2020
DOI: 10.1101/2020.07.13.20149328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Tocilizumab in Critically Ill Patients With COVID-19: A Quasi-Experimental Study

Abstract: Critically ill patients with COVID-19 may suffer from a cytokine release syndrome (CRS) characterized by remarkably high levels of interleukin 6 (IL-6). We assessed the effects of tocilizumab, an IL-6 receptor antagonist, on intra-hospital mortality and development of positive cultures in patients with COVID-19 admitted to the ICU. In this study, patients with COVID 19 admitted in the ICU who were treated with tocilizumab plus standard care were enrolled and compared to controls. Main outcome: 1) intra-hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A non-randomized controlled study (29 vs. 24) showed that after adjusting for age and mechanical ventilation, use of TCZ (400 mg, iv., two doses) was not associated with mortality of COVID-19 patients in ICU (OR = 3.97, 95% CI 0.28-57.2, P = 0.3), and no adverse events were reported that could be directly related to TCZ [79]. A propensity-score matched cohort study (74 vs. 148 severe/critical patients) found TCZ use was associated with a better overall survival (HR = 0.499, 95% CI 0.262-0.952, P = 0.035), but the length of hospital stay with TCZ was longer (dose: 8 mg/kg, HR = 1.658, 95% CI 1.088-2.524, P = 0.019).…”
Section: Implementation Considerationsmentioning
confidence: 92%
“…A non-randomized controlled study (29 vs. 24) showed that after adjusting for age and mechanical ventilation, use of TCZ (400 mg, iv., two doses) was not associated with mortality of COVID-19 patients in ICU (OR = 3.97, 95% CI 0.28-57.2, P = 0.3), and no adverse events were reported that could be directly related to TCZ [79]. A propensity-score matched cohort study (74 vs. 148 severe/critical patients) found TCZ use was associated with a better overall survival (HR = 0.499, 95% CI 0.262-0.952, P = 0.035), but the length of hospital stay with TCZ was longer (dose: 8 mg/kg, HR = 1.658, 95% CI 1.088-2.524, P = 0.019).…”
Section: Implementation Considerationsmentioning
confidence: 92%
“…Carvalhoet et al [ 95 ] compared the efficacy of TCZ in 28 patients with severe COVID-19 in the ICU and in 24 patients in the control group. Despite the initially more severe condition (the need for GC, mechanical ventilation, a marked decrease in gas exchange) of patients in the TCZ group, there was no increase in mortality (p = 0.3) and in the incidence of infectious complications in theTCZ group.…”
Section: Efficacy Of Anti-il-6r and Anti-il-6 Monoclonal Antibodies Imentioning
confidence: 99%
“…A total of 781 articles were identified in our search. Of these, 81 qualified for full-text review following title and abstract screening, of which 57 [11-67] were included in the analysis. The PRISMA flow diagram is detailed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Of the total of 57 studies included, 12 were prospective and 45, retrospective. In 30 of these cohort investigations, a control group was not described [10-38] and 27 added a comparison group [40-67]. The overall results provided data from 8,128 hospitalized patients with COVID-19: 4,021 TCZ-treated, in addition to standard of care (SOC) (including 711 patients admitted to ICU), and 4,107 only receiving SOC (including 694 patients admitted to ICU).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation